The Effect Of Aeration Pattern On Granular Ammonia Oxidizing Bacteria Development And Performance - Yusof, Muhamad Shaifol Mohd (Universiti Sains Malaysia, 2017)
Partial nitrification (PN) of aerobic granule usually carried out in constant aeration rate. In this study, the effect of reduction in aeration toward granular ammonia oxidizing bacteria (AOB) was studied in three different columns of sequencing batch reactor (SBR) (R1-R3). The effect of reducing aeration on granulation process was studied in Reactor 1 while the effect on PN was studied in Reactor 1, Reactor 2, and Reactor 3. Results show that Reactor 1 achieve 41 % of ammonium removal with average granule diameter of 1.55 mm. The concentration of nitrite at the effluent is 158 mg/L. The settling time plays an important role on the granulation process where it will acst as shear force. The settling time of Reactor 1 was reduced from five minutes to three minutes followed by two minutes and finally to one minute. The biomass concentration in Reactor 1 initially decrease and start to stabilize at day 57. Meanwhile, Reactor 2 achieved 50 % of ammonium removal with 2.77 mm average granule diameter and Reactor 3 achieved 42 % ammonium removal despite low biomass concentration. The concentration of nitrite presence in the effluent of Reactor 2 and Reactor 3 are 360 mg/L and 242 mg/L respectively.